Arenobufagin inhibits prostate cancer epithelial-mesenchymal transition and metastasis by down-regulating β-catenin. (September 2017) - Chen, Liping; Mai, Weiqian; Chen, Minfeng; Hu, Jianyang; Zhuo, Zhenjian; Lei, Xueping; Deng, Lijuan; Liu, Junshan; Yao, Nan; Huang, Maohua; Peng, Yinghui; Ye, Wencai; et al.
Graphical abstract: Abstract: Epithelial-mesenchymal transition (EMT) plays an important role in prostate cancer (PCa) metastasis; thus, developing EMT inhibitors may be a feasible treatment for metastatic PCa. Here, we discovered that arenobufagin and four other bufadienolides suppressed PC3 cell EMT. These compounds modulated EMT marker expression with elevating E-cadherin and reducing ZEB1, vimentin and slug expression, and attenuated the migration and invasion of PC3 cells. Among these five compounds, arenobufagin exhibited the most potent activity. We found that the mRNA and protein expression of β-catenin and β-catenin/TCF4 target genes, which are related to tumor invasion and metastasis, were down-regulated after arenobufagin treatment. Overexpression of β-catenin in PC3 cells antagonized the EMT inhibition effect of arenobufagin, while silencing β-catenin with siRNA enhanced the inhibitory effect of arenobufagin on EMT. In addition, arenobufagin restrained xenograft tumor EMT, as demonstrated by decreased mesenchymal marker expression and increased epithelial marker expression, and reduced the tumor metastatic foci in lung. This study demonstrates a novel anticancer activity of arenobufagin, which inhibits PC3 cell EMT by down-regulating β-catenin, thereby reducing PCa metastasis. In addition, it also provides new evidence for the development of arenobufagin as a treatment for metastatic prostate cancer.